THE EFFECTIVENESS OF E-LEARNING SYSTEM USING GOOGLE DOCS ON STUDENTS’ WRITING SKILLS IN NARRATIVE TEXT - Yusniar, Yusniar; Yauri, Andi Muhammad; Nur, Hasriati (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2022)
This paper investigates the effectiveness of e-learning system by using Google Docs feature in Google Classroom on students’ writing skills in narrative text. This research aims to finding out whether or not using Google Docs feature in Google Classroom is effective on students’ writing skills in narrative text at the eleventh grade of SMAN 26 Bone. The method of this research was quantitative research with a pre-experimental one-group pretest-posttest design. The sample of this research was selected by using purposive sampling technique. The instrument of this research was collected by using a writing test. In the pre-test, the students were given topic about writing narrative text with the theme of fable. The treatment in this research was given six times. In the post-test, the students were given the same instructions as in the pre-test. The result of analyzing data, the mean score in the pre-test was 55.74 and the mean score in the post-test was 80.65. The t-test showed that the sig. 2 tailed was .000, while the alpha was 0.05. It could be concluded that H1 was accepted and H0 was rejected. It can be stated that the use of Google Docs feature in Google Classroom is effective on students’ writing skills in narrative text Keywords: e-Learning, Google Classroom, Google Docs, narrative text, writing skills.